2019
DOI: 10.1105/tpc.19.00486
|View full text |Cite
|
Sign up to set email alerts
|

A Large Transposon Insertion in the stiff1 Promoter Increases Stalk Strength in Maize

Abstract: Stalk lodging, which is generally determined by stalk strength, results in considerable yield loss and has become a primary threat to maize (Zea mays) yield under high-density planting. However, the molecular genetic basis of maize stalk strength remains unclear, and improvement methods remain inefficient. Here, we combined map-based cloning and association mapping and identified the gene stiff1 underlying a major quantitative trait locus for stalk strength in maize. A 27.2-kb transposable element insertion wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 39 publications
1
35
0
Order By: Relevance
“…Similar results have been previously observed in maize, with reduced lignin content in the stem resulting in increased stalk lodging (Sun et al 2018). More recently, Zhang et al (2020) reported that downregulation of a maize gene, stiff1, resulted in thicker stalk cell walls with increased cellulose and lignin, which improved stalk strength and reduced lodging.…”
Section: The Impact Of Stem Compositionsupporting
confidence: 85%
“…Similar results have been previously observed in maize, with reduced lignin content in the stem resulting in increased stalk lodging (Sun et al 2018). More recently, Zhang et al (2020) reported that downregulation of a maize gene, stiff1, resulted in thicker stalk cell walls with increased cellulose and lignin, which improved stalk strength and reduced lodging.…”
Section: The Impact Of Stem Compositionsupporting
confidence: 85%
“…The most apparent function of lignin is providing mechanical strength and rigidity to the cell wall and facilitating the formation of xylem vessels to transport water and nutrients over a long distance (Zhao, 2016; Figure 2). In maize ( Zea mays ), an increase in the content of cellulose and lignin gives rise to greater stalk strength and resistance to stalk lodging, which threatens the yield of maize under high‐density planting (Zhang et al, 2020f). However, the ectopic lignification and lignin biosynthesis caused by the mutation of UGT72B1 , which is responsible for the glycosylation of monolignols, were found to lead to growth repression (Lin et al, 2016).…”
Section: Biofunctions Of Phenylpropanoid Metabolitesmentioning
confidence: 99%
“…Lodging due to stalk fracture can seriously interfere with the mechanical harvesting process of corn, and hence negatively impact yield [1]. Although many previous studies have used stalk stiffness as an indicator for resistance to lodging in crop plants, flexibility may be an indispensable trait in some cases [18,19]. Generally, the stalk breaks when wind pressure exceeds the load that a plant can withstand.…”
Section: Discussionmentioning
confidence: 99%